PEMBANGUNAN PARIWISATA EQUATOR PARK DAN PERUBAHAN SOSIAL BUDAYA EKONOMI MASYARAKAT - Iwan Ramadhan (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Every development activity always leads to better things. If development is not achieved, it will impact the society negatively. Through each of existing social changes, the existing community is expected to work together in carrying out any existing development activities, one of which is in the tourism sector, namely the construction of the Equator Park. The research method used is descriptive qualitative method, and the techniques used in data collection are observation and interviews. The purpose of this study is to see and find out the changes that have occurred in economic and socio-cultural fields that have existed in the community, especially in Jeruju Besar Village since the existence of the Equator Park tourist destination. The results indicated the occurrence of socio-cultural and economic changes leading to positive things for the people in Jeruju Besar village since the existence of the Equator Park tourist destination, and the community is required to be more creative and innovative in creating Equator Park tourist attractions and utilizing technology in introducing the tourist attractions.